A educação ambiental no ensino médio: estudo da sensibilização no Colégio Estadual Bartolomeu de Gusmão - Cedraz, Leandro de Oliveira (2015)
The city of Lauro de Freitas is an important city belongs to the metropolitan area of Salvador (RMS) which has important ecosystems and is undergoing an accelerated urban expansion process. This work was developed in state high school Bartolomeu de Gusmão, located in the municipality and has the environmental education course in their curriculum. Environmental Education can be an environmental awareness building tool on citizens and can contribute to a democratic and participatory environmental management. Thus, this study aims to evaluate the influence of environmental education discipline in changing environmental awareness in students of the first year of high school, which can foster democratic participation and student involvement in the environmental management process in the city, helping in building a healthy and balanced environment. This study was conducted through an exploratory research methodology by applying questionnaires, is characterized technically as a case study. It will be applied to students a questionnaire through which will be an estimate of the ecological and environmental awareness among the students who attend environmental education, which are attending the first year of high school, and students who have never had the discipline, but are already enrolled in the third year of high school. Our results showed that both groups of students had similar environmental concepts, which can be linked to the fact that students who did not have environmental education course be attending the 3rd year of high school, while students who attended the said course are in the first year of high school. Anyway, although comparisons of questionnaires answered by the two groups showed similar results, the formal environmental education can be seen as a factor which favors the ripening and improves the environmental perception of the student, making it politically able to intervene in decisions about environmental management in the city of Lauro de Freitas, since students in the group that had environmental education, although they are in the 1st year of high school and attending the course, already have ideas compatible with those of students of the 3rd year of high school. Thus, these results show that formal education can facilitate environmental sensitivity of students observe the environment and can be a tool which stimulates a larger engagement with the municipal environmental policies.